2010
DOI: 10.1007/s12325-010-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adherence and healthcare costs of insulin device (FlexPen®) versus conventional vial/syringe

Abstract: Without significant addition to the cost, insulin administration with FlexPen is associated with an improved adherence among patients who switched from vial-based insulin administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 13 publications
2
55
1
1
Order By: Relevance
“…Baser 12 had a low quality score, related to the lack of explicit ways to consider confounding factors and to not reporting confidence intervals in the results; they reported, however, standard deviations. Experimental studies had high risk of bias; the main issues were nonblinded design and insufficient explanation of randomization method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baser 12 had a low quality score, related to the lack of explicit ways to consider confounding factors and to not reporting confidence intervals in the results; they reported, however, standard deviations. Experimental studies had high risk of bias; the main issues were nonblinded design and insufficient explanation of randomization method.…”
Section: Resultsmentioning
confidence: 99%
“…A nonnaïve population 23,26 showed a less marked trend, with important heterogeneity (I 2 = 80%; χ 2 significant). Baser et al 12 reported that mean change in MPR in patients who exchanged vial for pen device was 0.22 ± 0.01, compared with 0.13 ± 0.36 for those who continued on vial (P = .0011). Two studies evaluated the proportion of patients with MPR > 0.80: Lee et al 23 showed difference favoring pen (0.546 vs 0.361; P < .01), and Buysman et al, 13 using a logistic regression model, found an OR = 1.39 (95% CI 1.04-1.85) favoring pen, after adjusting for age, gender, and comorbidities.…”
Section: Adherencementioning
confidence: 98%
“…Medication possession ratio (MPR) will be assessed by estimating the number of days that patients had possession of the study drug based on the prescription date and days of supply [35]. An MPR of 80% will define patients as being persistent on study medication.…”
Section: Outcomes Of Interestmentioning
confidence: 99%
“…Treatment adherence was measured by both the traditional medication possession ratio (MPR) and the adjusted MPR (aMPR), which takes into account the differences in insulin device package size. 27 For example, insulin glargine is packaged in either 10 mL vials with a total of 1000 units, or 3 mLF disposable pens in a package of 5 pens with a total of 1500 units. aMPR was calculated by multiplying the traditional MPR (the total days' supply of all filled study drug prescriptions in the analysis period, divided by the number of days in the analysis period) by the average days between prescription refills divided by the average days' supply for patients using insulin.…”
Section: Follow-up Study Outcomesmentioning
confidence: 99%